Prevalence and risk factors of moderate to severe hepatic steatosis in patients with rheumatoid arthritis: an ultrasonography cross-sectional case–control study - Gian Luca Erre (SAGE Publishing, 2021)
Background: The independent association between hepatic steatosis and rheumatoid arthritis is poorly defined. Methods: The presence of moderate to severe steatosis was assessed, using liver ultrasonography, in 364 consecutive non-diabetic subjects (223 patients with rheumatoid arthritis and 141 age- and sex-matched healthy controls). Adjusted multiple regression analysis was performed to explore the association between rheumatoid arthritis and moderate to severe steatosis in the overall sample and identify independent risk factors in the rheumatoid arthritis subgroup. Results: The prevalence of moderate to severe steatosis in the overall sample was 31.3%, with a significantly higher prevalence in patients with rheumatoid arthritis than healthy controls (38.7% versus 19.7%, p  < 0.0001). After adjustment for sex, age, cholesterol, triglycerides, body mass index, waist, hypertension and smoke, rheumatoid arthritis remained significantly associated with moderate to severe steatosis [odds ratio (95% confidence interval) = 2.24 (1.31, 3.84); p  = 0.003]. In the rheumatoid arthritis group, male sex, higher body mass index, higher triglycerides concentrations and higher cumulative dosage of methotrexate [odds ratio (95% confidence interval) = 1.11 (1.01, 1.23); p  = 0.026] were significantly associated with moderate to severe steatosis, while systemic inflammation, disease activity, use of steroids and biologics were not. Conclusion: Rheumatoid arthritis is independently associated with moderate to severe steatosis, with male sex, higher body mass index and cumulative dose of methotrexate being predisposing factors. Further prospective studies are warranted to confirm our findings and to investigate the effect of steatosis on liver outcomes in the rheumatoid arthritis population.